Pengaruh Pemenuhan Kebutuhan, Pemenuhan Harapan Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada Toko Duta Printer Kota Malang - Muhammad Sholehuddin; Budi Wahono; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractSholehuddin, Thesis Title, "The Influence of Fulfillment of Needs, Fulfillment of Expectations and Quality of Service on Customer Satisfaction at the Duta Printer Shop in Malang City". Strata 1 (S1) Management study program at the Faculty of Economics, Islamic University of Malang. 2017This study aims to determine the effect of Fulfillment of Needs, Fulfillment of Expectations and Quality of Service on Customer Satisfaction at the Duta Printer shop. The type of research used is a survey, the data collection method uses a questionnaire with a sample of 99 respondents who use products at the Duta Printer shop in Malang.The results of statistical calculations with multiple linear regression analysis can be shown by the regression equation Y = 0.879 + 0.163X1 + 0.094X2 + 0.115X3 + e. From the regression equation, it is known that the fulfillment of needs, fulfillment of expectations and service quality have a positive effect on customer satisfaction. This means that the better the fulfillment of needs, the fulfillment of expectations and the quality of services provided by the company, the greater the satisfaction felt by the customer. Keywords : Fulfillment of Needs, Fulfillment of Expectations, Quality of Service and Customer Satisfaction.